Why, when, and how to combine system dynamics with other methods: Towards an evidence-based framework. Issue 2 (3rd April 2018) - Zolfagharian, Mohammadreza; Romme, A. Georges L.; Walrave, Bob
Abstract: Combining system dynamics (SD) modelling with other research methods serves to articulate complex problems and explore potential solutions and policies. A growing number of studies draw on SD in combination with at least one other method, but there is hardly any knowledge about why, when, and how to make such combinations. We address this gap by conducting a systematic literature review of studies that have combined SD with at least one other method. Our findings are synthesised in an evidence-based framework that demonstrates why, when, and how SD is combined with other methods. This framework provides a point of reference for those who want to go beyond stand-alone SD modelling. In addition, this paper contributes to the multi-methodology literature by consolidating an area in which substantial experience in combining methods has been gained.